Transport system as an element of sustainable economic growth in the tourist region - Edna Mrnjavac (European Regional Science Association (ERSA), 2001)
Transport system is a whole composed of technical, technological, organisational, economic and legislative elements with the aim to perform transfer, loading and unloading of goods and passengers. Taking in consideration that most economic activities demand participation of certain transport system elements, any economic growth is impossible without an adequate transport system development. In order to secure environmental sustainable economic growth the economic policy subjects have to pay special attention to those parts of economy whose negative impact on environment cannot be neglected. One of them is transport. The influence of transport on environment consists in emission of gasses, smokes, noise and visual degradation of nature. A part of economic system that is extremely sensitive regarding environmental devastation is tourism. At the same time the efficiency of tourism strongly depends of the level of transport system development. On the example of interdependence of transport system and tourism in the Adriatic region the possibility of optimising the balance between these economic activities will be examined.
Keywords: 330